First insights into antimicrobial resistance, toxigenic profiles, and genetic diversity in Bacillus cereus isolated from Chinese sausages. (1st May 2023) - Xiao, Danyu; Tong, Cuihong; Yang, Tianmu; Huo, Zhipeng; Li, Yanhong; Zeng, Zhenling; Xiong, Wenguang
Abstract: Bacillus cereus is a common food-borne bacterial pathogen. This study was to designed the prevalence of B. cereus in Chinese sausages and evaluate its genetic diversity, toxigenic profiles, and antimicrobial resistance. Using bacteriological and biochemical detection tests, B. cereus was isolated from 12.63% (N = 49) of the total 388 samples. However, only 37 of the 49 isolates were simultaneously classified as the strictly B. cereus based on the classification of their genomes. Multi-locus sequence typing showed that the clonal complex was highly concentrated in CC142. Enterotoxin-encoding genes ( hblABCD, nheABC, entFM, and cytK ) were detected in all the strains. A total of 25 genes, associated with biofilm synthesis, were confirmed according to a computerized approach. In total, 89.19% of the isolates possessed only four resistance genes ( BcⅠ, BcⅡ, fosB, and vanZF ). Nevertheless, all isolates displayed resistance to three or more kinds of antibiotics. Moreover, three isolates were discovered to have tet (45) gene variants and were resistant to tigecycline. This study revealed the powerful potential of B. cereus to cause food poisoning in humans. The presence of multidrug-resistant B. cereus, especially with resistance to tigecycline, mediated by the tet (45) variant, poses a major threat to food safety and public health. Highlights: The first study of Bacillus cereus in Chinese sausage. The clonal complex of isolates was highly concentrated in ST-142 clonal complex. The enterotoxin genes associated with diarrheal symptoms were found in all isolates. Bacillus cereus isolates were all multidrug resistant. Three of the isolates had tet (45) variants and were resistant to tigecycline.